CVD-grown horizontally aligned single-walled carbon nanotubes: synthesis routes and growth mechanisms. - Ibrahim, I; Bachmatiuk, A; Warner, J; Büchner, B; Cuniberti, G; Rümmeli, M (2012)
Single-walled carbon nanotubes (SWCNTs) have attractive electrical and physical properties, which make them very promising for use in various applications. For some applications however, in particular those involving electronics, SWCNTs need to be synthesized with a high degree of control with respect to yield, length, alignment, diameter, and chirality. With this in mind, a great deal of effort is being directed to the precision control of vertically and horizontally aligned nanotubes. In this review the focus is on the latter, horizontally aligned tubes grown by chemical vapor deposition (CVD). The reader is provided with an in-depth review of the established vapor deposition orientation techniques. Detailed discussions on the characterization routes, growth parameters, and growth mechanisms are also provided.